Design, Fabrication And Characterization Of Rf Front-End 5g Wireless System - Mohamed Omar, Mohamad Faiz (2017)
The unexpected increase of cellular data growth has created absolute challenges for the mobile network service providers in order to counter with a worldwide wireless bandwidth shortage. The difficulty of mobile wireless bandwidth size shortage has attracted the interest towards the exploration of the underutilized millimetre-wave frequency spectrum for the future broadband mobile technologies. A wireless RF transceiver system operating at the millimetre wave (mm-Wave) frequency of 28 GHz for the 5G cellular network application is designed and fabricated. A series of RF front-end transceiver system consists of the RF transmitter and RF receiver. This RF front-end system provides a wide transmission bandwidth of 1000 MHz. The RF transceiver prototype is built using off-the-shelf components from the Avago Technologies and Hittite Microwave except for the 1 GHz and 28 GHz bandpass filters. The superheterodyne transmitter and superheterodyne receiver architectural designs are used to develop this RF front-end system design. There are two types of bandpass filter are designed in this project; lumped elements for low frequency at 1 GHz and Dielectric Resonator Filter (DRF) for mm-Wave frequency at 28 GHz. The lumped elements bandpass filter is designed at the centre frequency of 1 GHz with the transmission bandwidth of 1000 MHz. The 28 GHz bandpass filter is designed by using a combination of microstrip parallel-coupled filter and the dielectric resonators (DRs) made of CaCu3Ti4O12 (CCTO). The use of a dielectric resonator for the microwave circuit design directly can help to improve the performance of the circuit in terms of Q-factor and bandwidth size. The dielectric resonator bandpass filter produces a transmission bandwidth of 1000 MHz operating at the centre frequency of 28 GHz. The overall simulation design of the RF transceiver is carried out using Advanced Design System (ADS). Computer Simulation Technology (CST) is used to design the 28 GHz bandpass filter using dielectric resonators. The verification of design is accomplished through the RF transmitter and RF receiver hardware testing. The RF transmitter system works to up-convert an input IF signal at 1 GHz to an output RF signal at 28 GHz, while the RF receiver used to down-convert an input RF signal at 28 GHz to an output IF signal at 1 GHz. Based on the experimental results for the 28 GHz RF transceiver, the highest and lowest amount of IF signal output power are recorded at -13.12 dBm via 10 dB attenuator and -45.77 dBm via 50 dB attenuator when the IF signal input power is set at -20 dBm. The linearity of the IF signal output power is obtained around 80% when the 1 GHz IF signal is set at -20 dBm input power. The overall project of the 28 GHz RF front-end for the cellular network application is successfully designed and developed.